Češi - jací jsme a jací chceme být: Pohled dospívajících na sebe sama - Moravcová, Mirjam (Lidé města, 1999)
Self-image is a major part of collective conscience of modern national society. Whether built on ethnic, cultural and historical or national political characteristics, it is always among the instruments of self-consciousness, self-esteem and self-identification. It is part of the mental ownership by means of which even modern national societies build their identity, strengthen the consciousness of their solidarity, uniqueness as well as distinctiveness. It has a farce to mould a society, to help its integration, but also to highlight arising tendencies toward disintegration and disillusion from itself. In relation to other components with which members of a modem national society build the consciousness of their identity the own national image has to some extent a special position: it is not delineated by exact contours, it is not unchangeable, it combines in itself elements of diverse historical eras and it simultaneously includes some characteristics inserted in it by both the elite and ordinary bearers of the self-image. Its contours also accept those characteristics of group self-images with which groups of various opinions, and social and local origins build either their prestige, or, by contrast, which are rejected when different groups are regarded. As a rule, despite the resulting discrepancy, both characteristics are perceived as true. The self-image of a nation is superior to the group self-images. In its whole it does not express or reflect reality. It is a vision of who we would like to be. The basic tendency of this vision is not damaged even by negative characteristics. These are part of self-criticism heading for "self-cleaning". The presented study deals with the question of the current transformation of the self-image of a Czech among older schoolchildren. It is based on answers obtained through a field survey conducted in 25 towns or Bohemia, Moravia and Silesia (see Table III) in 1998. Views of pupils from ethnically-mixed schools in Prague, Brno, 19 district towns and for the sake of comparison also four smaller towns of the Czech Republic were recorded. The survey recorded answers from 3,438 children at the age of 13 14 years (pupils of the eighth classes of Czech elementary schools). However, only 3,058 of them said that their father was Czech. The survey is only based on the answers from these children. It reacts to the statements included in the replies to the open question What do you admire on Czechs? The respondents therefore themselves formulated their view and they were also given the opportunity not to reply to this question. More than one-fourth of them ignored the question. This largely concerned the children from Česká Kamenice, Ostrava, Sokolov, Děčín and Pardubice. The frequency of their lack of interest contrasted with a positive approach of children from other localities. However, another 15% reacted with the statements "I don't admire anything" (in particular children of fathers with higher or elementary education). Admiration for the Czech populatlon was therefore only displayed by 44 % of those polled. Testimonies by these 1,346 children made it possible to follow the three questions: a) what characteristics are ascribed by teen-age Czechs to the Czech nation; b) in what does their look at themselves differ from the view of the generation of adult people; and c) on what do they build their national self-identification and their relationship with their own national society. The analysis of answer led to the following conclusions: 1. There is no generally accepted image of Czech among the Czech youth under examination. There are only local models of the image. They strongly differ, especially in personal qualities ascribed to the Czech. Children from south and west Bohemia view Czechs are hard-working, while those from east Bohemian towns believe they are intelligent, and children from north Moravian towns regard them as frlendly. 2. From the viewpoint of intergenerational exchange the Czech youth aged thirteen to fourteen most often display self-stereotypes based on characteristics of mentality and intellectual abilities. There is the stereotype of wittiness and sense of humour and natural goodness, etc. 3. The image of the Czech, depicted by this youth, does not involve the self-stereotypes about cultural, artistic as well as professional capabilities. The same goes for stereotypes about industrial achievement of the Czech Lands and uniqueness of the Czech manufacturing, formerly deeply anchored in the consciousness of the Czech population. 4. When it comes to new elements, included by the children under examination into the image of their own nation, these were primarily the characteristics of patterns of behaviour, which meant ethically positive behaviour (generosity, solidarity), but also very negative qualities (rapacity, callousness, social passivity). These views, too, differ along regional lines (such as the statement about dishonesty in Prague, Hradec Králové, Klášterec n.Ohří, Frýdek-Místek). 5. The self-image of the Czech, proved in the children's attitudes, is strongly and primarily formed by the specific family, and secondly by the local society or, to be more precise, by the local social climate bound to local cultural traditions. An intensive influence of a friendly group of children from the same schoolclass was not proved. 6. The relationship with one's own national identity is built by children on the basis of a vague consciousness of cultural identity and common historical tradition. However, a major role is only played by the vision of a typical national drink (beer) and national dishes. 7. On the other hand, a need to declare oneself in the position of the Czech was voiced, though unasked, by more than 15 % of the children under observation. There were two markedly different positions: an uncritical admiration for the Czech nation on the one hand and pride of being Czech on the other. While the former position was often associated with xenophobic attitudes among some individuals, the latter was frequently accompanied with ethnic tolerance, an obliging attitude and effort to understand a different nation. Both positions had markedly differentiating local dimensions which almost never overlapped. Czech national feeling as a valid value was very often declared by the children from Prague, east and south Bohemian towns as well as from north Moravian and Silesian towns. 8. A part of the children called the Czech Republic a vital value of a Czech. The attitude toward one's own state was perceived by the children in a variety of reactions ranging from the criticism of the current reality to megalomaniac ideas about its international importance. 9. A small, but not negligible group of the children under examination refused to value an individual as a member of an ethnicity or a nation. It stood up for the position of cultural equality, free choice and persona! responsibility for behaviour, deeds and attitudes.